Red Mud-based Geopolymer and the Innovative Application - Yonghong Hao (Research Advances in Environment, Geography and Earth Science Vol. 7, 2024)
This chapter discussed the recent development of red mud-based geopolymer and its innovative application. These researches included the seepage penetration processes and the physical mechanism of red mud filtrate with heavy metal pollutants, the creation of an advanced cementitious material from solid waste red mud through alkali-thermal activation, the corrosion resistance and frost resistance of the red mud-based material, and the solidification effect on toxic heavy metals. An idea of granular thermodynamics was extended to describe the physico-mechanical characteristics of geotechnical materials like red mud-based geopolymer. This development addresses the utilization efficiency of red mud waste, the environmental pollution and controlling technology, and the purification technology of contaminated soils.